ChemInform Abstract: New Orthorhombic Derivative of CaCu5‐Type Structure: RNi4Si Compounds (R: Y, La, Ce, Sm, Gd—Ho), Crystal Structure and Some Magnetic Properties. Issue 5 (4th February 2014) - Morozkin, A. V.; Knotko, A. V.; Yapaskurt, V. O.; Yuan, Fang; Mozharivskyj, Y.; Nirmala, R.
Abstract The title compounds are prepared by arc melting of stoichiometric mixtures of the elements followed by annealing (argon, 1070 K, 200 h; quenching).